TRAINING ON THE MAKING OF HERBAL TEA FROM TEMURUI LEAVES AS AN EFFORT TO REDUCE THE RISK OF COVID 19 - Ulil Amna; Puji Wahyuningsih; Yulina Ismida (LPPM dan PM Universitas Samudra, 2021)
Alue Beurawe is a village located in Langsa City, which is one of the cities affected by the Covid-19 virus. Almost all sub-districts in Langsa City have felt the negative impact of the spread of the Covid-19 virus, so various ways are needed to prevent transmission of the virus. People who are prone to exposure to the virus are people who have a history of degenerative diseases, such as cancer, cholesterol, heart disease, asthma, and so on. All degenerative diseases are caused by the immune system being unable to fight the development of viruses in the human body. Therefore it is necessary to provide vitamin intake into the body that is able to fortify itself from the spread of harmful viruses, one of which is an antioxidant. Temurui is a local plant which is known to have high antioxidant activity. This plant can be found scattered throughout Aceh Province. The majority of Acehnese people use temurui plants as a spice for cooking, included the people in Alue Beurawe Village. Based on the previous research that has been done by the team, this temurui leaves have very good potential as an antioxidant which can reduce the risk of degenerative diseases and increase immunity. The manufacture of herbal tea made from temurui leaves is an effort to take advantage of the potential of the local natural resources of Alue Beurawe village in overcoming the risk of spreading the Covid-19 virus which is currently developing. Through PKM activities, it is hoped that it can increase the community's skills in processing temurui leaves into herbal medicine in the form of tea bags for private consumption as an alternative to reducing the transmission of the Covid-19 virus and can also be marketed to improve the community's economy. This PKM activity is carried out in the form of direct training with the Alue Beurawe community, especially member of PKK and unproductive housewives. After that, in this PKM activity, we hope that the community can produce herbal tea in a sustainable manner as a regional superior product`.